Caries Experience in Czech Preschool Children - E. Lenčová; Z. Broukal (Czech Dental Chamber, 2012)
Introduction, Aim: Childhood caries is the most common chronic childhood disease. The Czech Republic still belongs to countries with relatively high caries prevalence. The aim of the cross-sectional survey was to evaluate caries prevalence in the primary dentition of Czech preschoolers aged 3-6 years. Methods: The study design was approved by the competent Local Ethics Committee. The study was realized in 44 geographically stratified sites. The study sample consisted of preschool children aged 3-6 years, who were included in the study based on signed informed consent of their legal representatives. Epidemiologic examination of the subjects was performed in compliance with the WHO requirements for national oral health surveys including calibration exercise. A caries detection threshold used was a cavitated carious lesion. From dental records, the following oral health indicators were calculated: mean dmft per one child; mean dt; proportion of caries-free children; restorative index (ri) and significant caries index (SiC). Results: The study included 1232 children with a mean age 5.1 yrs (SD 0.81 yrs). Values of the above indicators: mean dmft: 2.55 (95% CI 2.22-2.66); mean dt: 1.87 (95% CI 1.62-2.00); proportion of caries-free children: 50.9%; ri: 21%; SiC: 6.9 (95% CI 6.60-7.25). Conclusions: Approximately half of the sample was caries-free. The SiC value was almost threetimes higher than mean dmft per child. Only one fifth of the teeth affected with dental caries were adequately treated. Further reduction of caries prevalence in the Czech preschool population cannot be expected without adequate caries-preventive interventions. Thus, oral health surveillance should be executed by regulatory authorities to help the policymakers get support for preventive initiatives and to enable further monitoring of childhood caries.